2013
DOI: 10.17221/24/2013-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Open characters of innovation management in the Hungarian wine industry

Abstract: Th e paper examines the relationship between the use of specifi c knowledge and economic success among Hungarian grape growers and wine makers. In the last decade, Hungary has been left behind by world trends as represented by the increasing share of the premium and super-premium wines (which utilise higher knowledge) in the export development. According to our survey, one cause of this might be the inappropriate use and management of knowledge and skills which is 'conditio sine qua non' for wine making. Th e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Networking may not be an efficient activity for service SMEs (Suh and Kim 2012). Among Hungarian SMEs, Török and Tóth (2013) found that the personal networks still play an important role in the success of SMEs. Managing multiple networks are challenging for SMEs.…”
Section: Networkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Networking may not be an efficient activity for service SMEs (Suh and Kim 2012). Among Hungarian SMEs, Török and Tóth (2013) found that the personal networks still play an important role in the success of SMEs. Managing multiple networks are challenging for SMEs.…”
Section: Networkingmentioning
confidence: 99%
“…However, Lichtenthaler (2008) found that most SMEs are still pursuing closed innovation over open innovation. Török and Tóth (2013) argue that firms that provide their ideas to external parties are more product innovative than non-providers. They found that mutual -rather than one-way exchange -relationships significantly raise the probability that SMEs experience a substantial benefit from contributing to other firms' new product development projects.…”
Section: Benefits Of Open Innovation In Smesmentioning
confidence: 99%
“…Another key internal factor determining work efficiency in agriculture, in particular in wine farms, is the level of their technical and technological advancement. As studies by Tomsik et al (2016) or Török and Tóth (2013) show, vineyard Proceedings of the 2019 International Scientifi c Conference 'Economic Sciences for Agribusiness and Rural Economy' No 3, Warsaw, 5-7 June 2019, pp. 76-83 farms with a significant degree of technology implementation are characterized by higher work efficiency.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, in the stage of idea implementation, it is suggested that SMEs use collaboration software, which is also abundant online. Collaboration software is nothing more than a digital network with only a few nodes, which may be a good solution for SMEs in develop ing countries: it is more affordable and applicable than innovation management software; it is ready for use outofthebox; it is easily manageable; and it is intimate enough to allow collaboration partners to gain trust, which is very important for the SMEs (Török & Tóth, 2013).…”
Section: Digital Network and Collaborationmentioning
confidence: 99%